2020
DOI: 10.3390/molecules25122786
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rutin in 5-Fluorouracil-Induced Intestinal Mucositis: Prevention of Histological Damage and Reduction of Inflammation and Oxidative Stress

Abstract: Intestinal mucositis, characterized by inflammatory and/or ulcerative processes in the gastrointestinal tract, occurs due to cellular and tissue damage following treatment with 5-fluorouracil (5-FU). Rutin (RUT), a natural flavonoid extracted from Dimorphandra gardneriana, exhibits antioxidant, anti-inflammatory, cytoprotective, and gastroprotective properties. However, the effect of RUT on inflammatory processes in the intestine, especially on mucositis promoted by antineoplastic agents, has not yet been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 87 publications
2
20
0
Order By: Relevance
“…In addition, p -coumaric acid [ 38 ], pyrogallol [ 51 ], cinnamaldehyde [ 52 ], ferulic acid [ 53 ] and cinnamic acid [ 54 , 55 ] present on the surface of Au@P-NPs have been reported for inducing thermogenesis and brown adipose tissue (BAT) activation in adipose tissues (ATs) to provide anti-obesity effects. Similarly, other cinnamyl acetate, rutin and catechin are known for anti-inflammatory activity [ 16 , 56 , 57 ] which can regulate metabolic inflammation in ATs of HFD-fed mice.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, p -coumaric acid [ 38 ], pyrogallol [ 51 ], cinnamaldehyde [ 52 ], ferulic acid [ 53 ] and cinnamic acid [ 54 , 55 ] present on the surface of Au@P-NPs have been reported for inducing thermogenesis and brown adipose tissue (BAT) activation in adipose tissues (ATs) to provide anti-obesity effects. Similarly, other cinnamyl acetate, rutin and catechin are known for anti-inflammatory activity [ 16 , 56 , 57 ] which can regulate metabolic inflammation in ATs of HFD-fed mice.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the height or the width of the villus indicates an increase in the surface area, which can better absorb the available nutrients, thereby regulating the nutritional status and improving the development and health of the poultry [ 35 ]. Fideles et al [ 36 ] pointed out that pretreatment with rutin (100 and 200 mg/kg) showed a marked reversal in villi shortening in the duodenum and the jejunum in mice of 5-Fluorouracil (FU) induced experimental intestinal mucositis; however, all rutin doses failed to reverse the villi shortening caused by 5-FU in the ileum. Additionally, Zhang et al [ 37 ] reported that dietary rutin (250 mg/kg) and rutin (1000 mg/kg) in weaned mice for 21 days increased jejunum villus height, indicating that rutin improved intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with our study, where we observed that the potent anti-tumor effect detected by 5-FU was in parallel with a concomitant increase in the levels of the in ammatory biomarkers NO, TNF-α, IL-6, IL-1b, and NF-κB in both serum and ascetic uid. Stimulation of systemic in ammation by chemotherapies could be attributed to tissue damage and cell apoptosis as a result of the cytotoxicity effect, and also the elevation of reactive oxygen species through inducing the myeloperoxidase enzymes (MPO), a neutrophil marker [33][34][35]. Alternative therapeutics that can impair the side effects of 5-FU, without affecting treatment e ciency are urgently needed.…”
Section: Discussionmentioning
confidence: 99%